El tampering o data diddling, una vulneración a la libre competencia, al mercado y al bienestar económico en general - Tinajero Bolaños, Diego Fernando (2016)
The Antitrust Law is a fiend of Law that that even because of its importance and economical transcendent. It appeared in our country at the beginning of 2008. For this reason, the rules an customs referring to this subject have not being as analyzed and developed as the other subjects of law, especially with the newest fiends in law that have born with the globalization phenomena and the new production factors. With the growth of the industrial and society development, technology became one of the most important and essential tools, which was a privilege for a few people and the desire of all the population at its beginnings. Undoubtedly, technology has become an essential role in the economy, for this reason, a need to regulate this instrument through the use of intellectual property and penal branches for the misuses was the best option, and depending of the impact of the damages caused the Antitrust Law is used. This work tries to analyze the illegal actions of informatics, its origins and effects in the Antitrust Law in Ecuador